Society News Vol.23(2) - Editor, The (Bangladesh Journal of Obstetrics & Gynaecology, 2010)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if !mso]> <![endif]--> <!--[if gte mso 10]> <![endif]--> DOI: 10.3329/bjog.v23i2.4967 Bangladesh J Obstet Gynaecol, 2008; Vol. 23(2) : 84-85